AN ANALYSIS OF STUDENTS’ HANDWRITING THROUGH GRAPHOLOGY TO MOTIVATE STUDENTS BASED ON ITS LEARNING STYLE - Septiana Rifda Saskia; Hendra Hendra; Aa Qona’atun (FKIP, Universitas Banten Jaya, 2022)
The objectives of this study were to find out students' learning styles, character or personality, and learning motivation in English by using graphology as a method of analysis. This research used a qualitative approach. The method used in this research was content analysis. This research was conducted in SMK PGRI 3 Kota Serang with a total of the participant is 10 students. The data was obtained by collecting data of students’ handwriting and through the interview of confirming the accuracy of the analysis. The results of this research were: the accuracy of students' characters and personalities is 82,6% and the accuracy of students' motivation is 77,5%. As a final result, the average students have standard to high motivation in learning English.